The effect of the difference in the control pattern of an educational program on developing the digital image processing skills of fifth grade students in the subject of information technology - Albalushi, Ali Salim Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to measure the digital image processing skills of fifth-grade students with a subject of information technology. The study was conducted on a random sample of fifth-grade students in Al-Mabrad School for Basic Education in the Wilayat of Al-Suwaiq in Al-Batinah North Governorate in the Sultanate of Oman, which numbered (60) students during the second semester of the academic year. 2019-2020 AD, the semi-experimental approach and the data collection tool represented in the observation card were used, and the study found statistically significant differences (α£0.05) between the mean scores of the two experimental study groups in the post application of the observation card in digital image processing skills in favor of a pattern Learner control with mentoring.
Keywords: Control patterns; Educational control; Multimedia; Educational software